2012
DOI: 10.1242/jeb.071076
|View full text |Cite
|
Sign up to set email alerts
|

Experience, corpulence and decision making in ant foraging

Abstract: SUMMARYSocial groups are structured by the decisions of their members. Social insects typically divide labour: some decide to stay in the nest while others forage for the colony. Two sources of information individuals may use when deciding whether to forage are their own experience of recent task performance and their own physiology, e.g. fat reserves (corpulence). The former is primarily personal information; the latter may give an indication of the food reserves of the whole colony. These factors are hard to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(43 citation statements)
references
References 44 publications
1
40
0
1
Order By: Relevance
“…Ants that possess greater fat reserves might also survive longer when facing adverse conditions. Measures of fat content in our study confirmed the pattern of 'lean forager-corpulent inner-nest worker', which is common in social insects (Seeley, 1995;Schulz et al, 1998;Markiewicz and O'Donnell, 2001;Tschinkel, 1998;Blanchard et al, 2000;Smith et al, 2011;Tibbetts et al, 2011;Robinson et al, 2012;Mersch et al, 2013;Bernadou et al, 2015) and suggests that inner-nest workers survived longer due to their high fat reserves. When fed an imbalanced diet, foragers that remained foragers lost a considerable amount of fat and foragers that reverted to inner-nest tasks did not gain any fat.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Ants that possess greater fat reserves might also survive longer when facing adverse conditions. Measures of fat content in our study confirmed the pattern of 'lean forager-corpulent inner-nest worker', which is common in social insects (Seeley, 1995;Schulz et al, 1998;Markiewicz and O'Donnell, 2001;Tschinkel, 1998;Blanchard et al, 2000;Smith et al, 2011;Tibbetts et al, 2011;Robinson et al, 2012;Mersch et al, 2013;Bernadou et al, 2015) and suggests that inner-nest workers survived longer due to their high fat reserves. When fed an imbalanced diet, foragers that remained foragers lost a considerable amount of fat and foragers that reverted to inner-nest tasks did not gain any fat.…”
Section: Discussionsupporting
confidence: 82%
“…Second, there is a further division of labour among workers depending on genetic components, morphology, age and physiological status (Hölldobler and Wilson, 1990). In many species, for example, older and lean workers are the ones in charge of foraging for the entire colony, whereas younger and corpulent individuals stay in the nest (Seeley, 1995;Schulz et al, 1998;Markiewicz and O'Donnell, 2001;Tschinkel, 1998;Blanchard et al, 2000;Smith et al, 2011;Tibbetts et al, 2011;Robinson et al, 2012;Mersch et al, 2013;Bernadou et al, 2015). Nevertheless, division of labour among workers remains highly flexible in social insects.…”
Section: Introductionmentioning
confidence: 99%
“…1). Ant species may differ substantially in the extent of the influence of age on behavior and its underlying physiological processes (Sendova-Franks and Franks 1993, 1995; Seid and Traniello 2006; Muscedere et al 2009, 2011; Robinson et al 2012, e.g.). The role of age in task performance has sparked controversy (Tofts and Franks 1992; Robson and Beshers 1997; Traniello and Rosengaus 1997); in some ants the effects of age on behavior may be weak (Sendova-Franks and Franks 1993, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…For example, Heijne and Sanfey (2015) reported that the effect of prior beliefs on stay/leave decision‐making was much less pronounced in a social than in a nonsocial context. For rodents, which are highly social experimental animals, social situations affected their decision‐making including mate choice, territorial scramble and food foraging (Dall & Wright, 2009; Robinson, Feinerman, & Franks, 2012; Westneat, Walters, McCarthy, Hatch, & Hein, 2000). The findings from Hillman and Bilkey (2012) suggested that the anterior cingulate cortex (ACC) is an important cost–benefit domain for encoding spatial and competitive decision‐making in rats.…”
Section: Introductionmentioning
confidence: 99%